Management Processes in the Development of the Socio-Economic Environment of the Region - BABOSHKINA, Anastasia A.; SAVINA, Natalia P.; MOROZOV, Ivan V. (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).02, 2018)
The global economic crisis, many internal problems of the national economy, threats and negative impact of the external environment are the main causes of economic instability at the national level, and as a result, instability at the regional level. In this regard, the basic condition of regional development is a public policy that will ensure sustainable socio-economic development of regions on the basis of their potential and possible threats from the external environment. In modern society feel the need to research aimed at solving problem the development of society from a position of respect social priorities, balancing the interests of the government, civil society, the business community, conservation of ecological balance. Today require state regulators that will allow to organize the process of strategic management of development of regions taking into account the interaction of many internal and external factors affecting their development. The development of theoretical and practical issues concerning the choice of strategy of development of regions and mechanisms to achieve policy objectives, approaches to the assessment of the degree of achievement of goals and objectives is a critical task in the development of regional self-government. The increasing need of renovation and improvement of organizational support of strategic management of socio-economic development of the regions in compliance with the main guidelines of economic reforms in the Russian economy through the development of strategic partnership of government, community, business community, and the need to improve the methodical support of assessment of effectiveness of strategic management of region's development and the degree of stability of its development was determined by the relevance of the chosen topic.